Território estético e território político, corpo e insurreição através da arte, un estudo a partir da obra de Tatsumi Hijikata - Coletty, Viviana de Souza (2017)
The present study comes with the intention of deepening understandings of relations between political dynamics of territorial creation and the creation of artistic languages, from the analysis of the Tatsumi Hijikata’s work. The central question of our work come into sight through an interdisciplinary study that implicates foundations of philosophy, aesthetics, phenomenology and semiotics. Among the studied authors represent mainly Bergson, Bachelard, Deleuze, Guattari, Uno, Tancelin and Greiner. Based in concepts of deterritorialisation and reterritorialisation of Deleuze and Guattari, our hypothesis is that in front of a type of deterritorialisation, which puts a group of people in an abrupt changing contexts situation, there would be a consequent reterritorialisation. Between other forms this reterritorialisation could manifest itself through the insurrection of subjectivities towards the world. This insurrection, in certain cases, would be established through the actualisation of aesthetic territories. When these manifestations are shared with public, it would be as if the insurrection of a new aesthetic territory comes to light. This idea, of an aesthetics territory, we developed during this study, to help with our thought’s évolution. Through butô and a large written production, Hijikata questions the concept of the body, and the functions of art, in a way which seems to meet in a several ways with concepts created and/or developed by Deleuze and Guattari, relatively at the same epoch. Concepts as body without organs, devenir, and immanence plan, are brought into analysis in the course of this study, with proposals developed by Hijikata. Beyond the resonances of a period of crisis in a culture, what we want to analyse is possible resonances into political panorama in long term, provoked by aesthetics experiments.